Startups and Consumer Behavior: Purchasing Intentions Toward Products and Services of New Startups in Kathmandu Valley - Shakya, Sagun; Devkota, Niranjan; Paudel, Udaya (Economic Journal of Development Issues, 2024)
Entrepreneurship is widely acknowledged as a fundamental driver of economic progress, with startups serving as platforms where entrepreneurs transform their innovative ideas into reality, delivering products and services to the world. Consequently, startups are viewed as carriers of innovation. This study investigates consumer purchase intentions toward products and services offered by startups. The Theory of Planned Behavior (TPB) is applied in this study to analyze customers’ intentions regarding startup products and services. An explanatory research design was employed to examine cause-and-effect relationships among customers in the Kathmandu Valley. Using a convenience sampling technique, a total of 218 customers were interviewed through a structured questionnaire, with data collected using Kobo Toolbox. Structural Equation Modeling (SEM) was conducted to assess customers’ purchasing intentions using SPSS and SPSS AMOS software. The SEM results indicate that attitude, subjective norms, and perceived behavioral control have significant causal relationships with customer intentions toward products and services offered by startups in the Kathmandu Valley. The findings reveal that consumers' surrounding environments, including family, peers, and influencers, significantly impact their purchasing intentions.